Direct Amination of Cobaltocenium Hexafluoridophosphate via Vicarious Nucleophilic Substitution - Jochriem, Markus (Organometallics, 2019)
[Image: see text] In this communication we report a convenient, as short as possible synthesis of aminocobaltocenium hexafluoridophosphate, a very useful compound for further functionalization in cobaltocenium chemistry. Via vicarious nucleophilic substitution of hydrogen of cobaltocenium hexafluoridophosphate with 1,1,1-trimethylhydrazinium iodide as nucleophile bearing its own leaving group, a one-step amination of cobaltocenium in 50% isolated yield is possible, a major improvement over the standard multistep procedure involving common Curtius rearrangement chemistry.